Image: from the cinema to the performance - Sehn, Carina; Zordan (Federal University of Rio Grande do Sul, Porto Alegre /RS, Brazil), Paola (Revista Brasileira de Estudos da Presença, 2022)
In the scope of a research on the body arts, the text approaches the issue of image representation in face of corporeal forces. With Deleuze’s philosophical studies on cinema, we bring his image taxonomy, which passes from a movement-image to a time-image, and we also consider theater to analyze how an image is launched from a stratified and moralizing representation to a performative and resonating image. The work of contemporary artists allows and makes us think an image in its relation with the new, with what is impossible to restrain, with images produced by the art of performance, by a body which creates images successively.